A RISK-BASED CONTROL FRAMEWORK FOR SAND PRODUCTION DURING OIL AND GAS OPERATIONS - Tanabayeva, Saya (Nazarbayev University School of Engineering and Digital Sciences, 2021)
Sand extraction in oil production is one of the most important problems in the world. The main reasons for this error are the low quality of uniformity, the lack of foresight of this problem, weak consolidation, and others. This has a negative impact on the development of oil and gas fields, and can lead to consequences of different levels. Sand extracted from wells can damage or disable production or processing equipment. Therefore, companies operating in these areas should prevent or minimize the consequences by analyzing the forecast and monitoring of sand production. These methods are considered and constructed depending on the characteristics of the well or formation. The main goal of the work is to develop and build an algorithm and system for assessing and managing risks arising from sand mining at the stages of drilling and oil and gas production. The results of the study showed that the use of the bayesian network with the help of genie software makes it possible to create a framework for analyzing the actions of control methods on the production of sand.
Keywords: oil production; sand extraction; production of sand; Research Subject Categories::TECHNOLOGY; Type of access: Gated Access